Investigating the Effectiveness of Using Charade Games in Teaching Vocabulary for EFL Learners - Rohmatussholihah, Yeni; Candraloka, Olyvia Revalita (Pascasarjana Universitas Negeri Makassar, 2025)
This study examines the effectiveness of using charades as a teaching strategy to enhance vocabulary mastery among sixth-grade students at Madrasah Ibtidaiyah Sadamiyyah Guyangan Bangsri Jepara. A pre-experimental design with a one-group pre-test and post-test approach was employed, involving 22 purposively selected students. Data were collected using a vocabulary test consisting of 30 multiple-choice and 10 short-answer questions. The findings indicate a significant improvement in students' vocabulary mastery, with the mean pre-test score increasing from 64.23 to 78.23 in the post-test. A paired sample t-test revealed a statistically significant difference (Sig. (2-tailed) = 0.000, p < 0.05), confirming the positive impact of the charades game. The study highlights that charades promote student engagement, motivation, and peer interaction, making vocabulary learning more effective and enjoyable. Furthermore, the results suggest that charades facilitate a dynamic and stress-free learning environment, reducing student anxiety while improving retention and recall of new words. The findings of this study suggest that incorporating interactive and engaging activities like charades can enhance vocabulary acquisition in EFL classrooms. Teachers can utilize this method to foster active participation and collaboration among students, making the learning process more immersive. Additionally, charades provide an alternative to traditional rote memorization, encouraging meaningful language use and long-term retention. Educators should consider integrating game-based learning strategies to create an interactive and student-centered classroom environment that supports vocabulary development.